Metabolic and cardiorespiratory reactions in tennis-players in laboratory testing and under sport-specific conditions - Smekal, G.; Baron, R.; Pokan, R.; Dirninger, K.; Bachl, N. (1995)
Metabolic and cardiorespiratory reactions were investigated during a sport-specific incremental field test (FT) for tennis and compared with a treadmill step test (TT) in a group of 13 trained male tennis players. In both the FT and the TT lactate acid (La), heart rate and oxygen uptake (VO2) were measured. VO2 was determined using a portable telemetric system (K2, Cosmed, Italy). Aerobic- (AT) and anaerobic threshold (ANT) at a blood lactate concentration of 2 mmol/l and at 4 mmol/l respectively was indicated to characterize the endurance capacity of the athletes. In both FT and TT, minimum value of lactate equivalent (LE(min)), measured in every exercise test, was also registered. At AT and ANT values for HR (AT: p < 0.001; ANT: p < 0.001) and VO2 (AT: p < 0.001; ANT: p < 0.001) were significantly higher in FT than in TT at submaximal loads. At LE(min) only higher values for HR (p < 0.05) were registered in FT. In contrast to maximum range significantly higher values for VO2 (p < 0.001) could be seen in TT (there were no significant differences for HR). Comparing maximum lactate (La(max)) subjects reached a higher lactate (p < 0.05) in TT. A particular aim of our investigation was to characterize the individual cardiopulmonal and metabolic adaptation of tennis players, considering sport-specific criteria. As a result, differences in cardiorespiratory and metabolic adaptations could be determined between laboratory TT and FT. This finding seems to point to the fact that, using field testing in addition to laboratory exercise testing, makes a better judgement of aerobic and anaerobic endurance under sport-specific conditions possible. Furthermore, it was important for us to put data, determined in the field test into practice, using the given pattern of the field test as an element of training. This kind of training has the advantage of combining an individually intensity-controlled specific endurance training for tennis with a training of technical skills. Wien Med Wochenschr 1995;145(22):611-5